Schoolhouse mystery eaudiobook - Warner, Gertrude Chandler (The Boxcar Children, 2012)
Henry, Jessie, Violet, and Benny once lived on their own in a boxcar... The Boxcar Children are spending the summer in a tiny, quiet New England fishing village. The little schoolhouse doesn't have a proper teacher, so the Aldens are teaching! There's also a very old library where nobody ever goes — nobody, that is, except for a mysterious stranger. For such a small town, Port Elizabeth has a lot of secrets! Look for more Boxcar Children adventures in this exciting series.